ANALISIS POSISI EKSPOR KOPI INDONESIA DI PASAR DUNIA - Sari, Desi Ratna; Tety, Ermi; ', Eliza (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
The purpose of this study was to analyze the development of Indonesia's coffee exports and analyze the position of Indonesian coffee in the world market. The data used in this study was a secondary data export raw coffee Indonesia, Brazil, Vietnam and Colombia during the period 2001-2012. The data was taken from the land area, production, price, value and volume of exports of coffee in the world market. Supply and demand of coffee in the world market as long 2001-2012, overall was increase every years. Coffee offer influenced by land area, production, export value, export volume and the price of coffee by coffee producing countries in the world like Brazil, Vietnam, Colombia and Indonesia. The demand of coffee in the world during 2001-2012 has increase by sign of consumption and the amount of imports coffee in the world more increasing. The FOB price for Brazil, Vietnam and Indonesia has increase significantly during 12 years, accept Colombia. However, the Indonesian coffee still can be the price leader like Brazil, that affect the price of coffee in the world. Keywords: coffee, position, production, export value, export volume.